2019
DOI: 10.3390/ijerph16071092
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Antimony with Natural Organic Matter: Performance Evaluation during Coagulation-Flocculation Process

Abstract: The presence of natural organic matter (NOM) in drinking water sources can stabilize toxic antimony (Sb) species, thus enhancing their mobility and causing adverse effects on human health. Therefore, the present study aims to quantitatively explore the complexation of hydrophobic/hydrophilic NOM, i.e., humic acid (HA), salicylic acid (SA), and L-cysteine (L-cys), with Sb in water. In addition, the removal of Sb(III, V) species and total organic carbon (TOC) was evaluated with ferric chloride (FC) as a coagulan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 55 publications
(104 reference statements)
7
29
0
Order By: Relevance
“…Other literature data showed better ligand activity of para‐substituted pyridine in sorption processes of Pt(IV) compared to ortho‐substituted aminopyridine . In addition, according to our measurements, the presence of hydrophobic disiloxane moiety enhanced the affinity of the ligand for Pt(IV), as other studies have revealed for hydrophobic ligands, such as humic acid, which forms stronger complexes with Sb than hydrophilic ligands …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other literature data showed better ligand activity of para‐substituted pyridine in sorption processes of Pt(IV) compared to ortho‐substituted aminopyridine . In addition, according to our measurements, the presence of hydrophobic disiloxane moiety enhanced the affinity of the ligand for Pt(IV), as other studies have revealed for hydrophobic ligands, such as humic acid, which forms stronger complexes with Sb than hydrophilic ligands …”
Section: Resultsmentioning
confidence: 99%
“…[49] In addition, according to our measurements, the presence of hydrophobic disiloxane moiety enhanced the affinity of the ligand for Pt(IV), as other studies have revealed for hydrophobic ligands, such as humic acid, which forms stronger complexes with Sb than hydrophilic ligands. [50] For comparison, the complex formation ability of these ligands with PdCl 2 and RuCl 2 (DMSO) 4 was studied using the Hildebrand-Benesi method, and the found stability constants are also summarized in SCHEME 1 Chemical structures of the ligands used in this study Table 1. It can be observed that the affinity for Pd(II) was better in the case of model ligands compared with the siloxane ones, but the para-substituted pyridyl ligands still gave better results in each mini-series.…”
Section: Synthesis Of Pt(iv) Complexesmentioning
confidence: 99%
“…These model organic ligands that is, HA and SA had been widely used to simulate different water characteristics. Moreover, these model substances were obtained from commercial sources and have been widely used to provide consistent experimental conditions [29,30,31]. Prior to the binding and coagulation experiments, the total organic carbon (TOC) contents for HA and SA (10 mg L −1 each) were analyzed to be 4.17 and 2.40 mg C/L, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The organic ligand bound As was characterized by calculating the difference between total and free As species in water. The procedure was previously described in detail elsewhere [31,33]. Furthermore, the bonding features of pristine HA, SA and As(III, V) species as well as As-organic ligands composite complexes and FC composite flocs were determined using Fourier Transform Infrared Spectroscopy (FT/IR-4700, spectroscopy; JASCO Analytical Instruments, Easton, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The chelating effect of FAs can reduce the cation-positive charge and facilitate the migration of micronutrients to the plant. On the other hand, the lack of knowledge on interactions and complexing properties of FAs or other fractions of soil organic matter can pose a risk of heavy metal migration [16,17] and stabilize toxic species in drinking water [18,19]. Translocation of heavy metals to plants can increase the risk of food-chain contamination [20].…”
Section: Introductionmentioning
confidence: 99%